The Role Of Pt. Pertamina Ep Asset 2 Field Pendopo In The Field Of Socio-Economic Community In Talang Ubi District Pali Regency In 2003-2015 - Ari Supriyatno; Farida Farida; Supriyanto Supriyanto (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This paper is raised about the role of PT.Pertamina EP Asset 2 Field Pendopo in the field of socio economic community in Talang Ubi Sub-District PALI Year 2003-2015. The problems in this research is how the establishment of PT.Pertamina EP Asset 2 Field Pendopo in 2003, and how the role of PT.Pertamina EP Asset 2 Field Pendopo in the field of social and public economic field. In the social field observes the role of education, religious, health, and other social fields. While the field of economy covers how the role of the company in improving the community's economy kecang talang ubi.